2016
DOI: 10.1007/s11832-016-0797-6
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and function in middle-aged individuals with thalidomide embryopathy

Abstract: ObjectivesThe aim of this study was to evaluate the effect of limb malformations on health-related quality of life (HRQL) and function of the extremities in middle-aged individuals with thalidomide embryopathy (TE). Between 1959 and 1962, approximately 150 children with multiple malformations were born in Sweden following the maternal intake of thalidomide during pregnancy, of whom 100 survived.MethodsThirty-one individuals with TE underwent evaluations of musculoskeletal manifestations by clinical examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 26 publications
2
16
2
Order By: Relevance
“…Similar results were reported by study conducted in Sweden. Ghassemi Jahani et al (2016) reported that the physical aspects of QOL in many of individuals were significantly lower than those of the national reference population, but that the mental aspects of QOL were not significantly affected. Saito (2002) compared patients with TE with different types of disability and they found that total GHQ score was higher in the hearing impaired group in 2000.…”
Section: Discussionmentioning
confidence: 93%
“…Similar results were reported by study conducted in Sweden. Ghassemi Jahani et al (2016) reported that the physical aspects of QOL in many of individuals were significantly lower than those of the national reference population, but that the mental aspects of QOL were not significantly affected. Saito (2002) compared patients with TE with different types of disability and they found that total GHQ score was higher in the hearing impaired group in 2000.…”
Section: Discussionmentioning
confidence: 93%
“…Peters et al [11], reported that Thalidomide survivors had a mean aggregate physical score of 29.6 and a mean aggregate mental health score of 47.8. A Swedish study of 31 Thalidomide survivors [40] also found that their physical health related quality of life was significantly lower than the general population, although their mental health related quality of life was similar.…”
Section: Discussionmentioning
confidence: 99%
“…The anti‐emetic capacity of the drug opened another treatment field of this drug for morning sickness in pregnant women. It is estimated that approximately 40% of infants with TE died before their first birthday (Ghassemi Jahani, Karlsson, Brisby, & Danielsson, ).…”
Section: Chemical Agentsmentioning
confidence: 99%